The Swedish Family‐Cancer Database 2009: prospects for histology‐specific and immigrant studies - Hemminki, Kari; Ji, Jianguang; Brandt, Andreas; Mousavi, Seyed Mohsen; Sundquist, Jan (International journal of cancer, 2010)
The Swedish Family‐Cancer Database comprises a total of 11.8 million individuals covering the Swedish population of the past 100 years. Version VIII of the Database is described in the present article. Cancer cases were retrieved from the Swedish Cancer Registry for the period 1958–2006, including more than 1 million first primary cancers. The number of familial cancers in offspring is 14,000 when a parent was diagnosed with a concordant (same) cancer and the number of concordant siblings was 6,000. From the year 1993 onwards histopathological data according to the SNOMED classification were used, which entails advantages for certain cancers, such as breast cancer. Even though the specific morphological classification only covers a limited number of years, it does cover most familial cancers in the offspring generation. The Database records the country of birth for each subject. A total of 1.79 million individuals were foreign born, Finns and other Scandinavians being the largest immigrant groups. The cancer incidence in the first‐generation immigrants was compared to that in native Swedes using standardised incidence ratios (SIRs) to measure relative risk. The SIRs ranged widely between the immigrant groups, from 1.9‐fold for myeloma to 25‐fold for melanoma. The differences in SIRs were smaller in the second‐generation immigrants. The usefulness and the possible applications of the Family‐Cancer Database have increased with increasing numbers of cases, and the numerous applications have been described in some 300 publications. Familial cancer studies are in the stimulating interphase of the flourishing disciplines of genetics and epidemiology.